New Insights Into Cell Culture Technology 2017
DOI: 10.5772/66903
|View full text |Cite
|
Sign up to set email alerts
|

Concepts for the Production of Viruses and Viral Vectors in Cell Cultures

Abstract: The industrial-scale manufacturing of viruses or virus-like particles in cell culture is necessary for gene therapy and the treatment of cancer with oncolytic viruses. Complex multistep processes are required in both cases, but the low virus titers in batch cultures and the temperature sensitivity of the virus particles limit the production scale. To meet commercial and regulatory requirements, each process must be scalable and reproducible and must yield high virus titers. These requirements are met by establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 80 publications
1
10
0
Order By: Relevance
“…Thus, a correlation between the dielectric signal and the offline determined cell concentration of the infected cells was not possible (Grein, Weidner, & Czermak, 2017). Thereby, we found, that the physical properties of the cell in the electric field of the sensor probe changed due to the alteration of the cell morphology in cause of the virus infection.…”
Section: Several Other Viruses Have Been Investigated As Virotherapymentioning
confidence: 86%
See 1 more Smart Citation
“…Thus, a correlation between the dielectric signal and the offline determined cell concentration of the infected cells was not possible (Grein, Weidner, & Czermak, 2017). Thereby, we found, that the physical properties of the cell in the electric field of the sensor probe changed due to the alteration of the cell morphology in cause of the virus infection.…”
Section: Several Other Viruses Have Been Investigated As Virotherapymentioning
confidence: 86%
“…Thereby, we found, that the physical properties of the cell in the electric field of the sensor probe changed due to the alteration of the cell morphology in cause of the virus infection. Thus, a correlation between the dielectric signal and the offline determined cell concentration of the infected cells was not possible (Grein, Weidner, & Czermak, 2017). Reversely, this means that the change in the permittivity signal may be a good parameter for online monitoring of the infection process and, in consequence for process control.…”
Section: Several Other Viruses Have Been Investigated As Virotherapymentioning
confidence: 99%
“…This is similar to the report of Lawal et al [20] who found that vvIBD virus propagated in stirred tank bioreactor did not show molecular change in their VP2 protein. Other researchers did not report any change in the characteristics of the bioreactor propagated viruses which suggests that use of bioreactor for propagation of vaccine virus is suitable for large volume production of vaccines [41,59,60]. However, there was a point substitution in the hexon gene of UPM08136CELP20B1 which led to change in the amino acid residues at position 2 from cysteine to glycine.…”
Section: Discussionmentioning
confidence: 97%
“…Cell-free systems are also difficult to produce in laboratory conditions, but there are various kits for the expression of cell-free proteins available for sale. It can be concluded that the process of VLPs is not easy and requires special laboratory conditions, which complicates their large-scale production [231][232][233].…”
Section: Virus-like Particles (Vlps)mentioning
confidence: 99%